Correlaciones y análisis geológicos entre muestras de dragas recolectadas durante la campaña amadeus (2005) y muestras de tierra tomadas entre jama y Esmeraldas - Coello Baldeón, Xiomara Isabel (2009)
In the current study, several geological analyses were performed with the collected dredge samples during the AMADEUS (2005) campaign and with samples taken from the Ecuadorian northern coastal margin, in the area of Jama and Esmeraldas. Studies consist of macroscopic observations of facies, fractures, grain size, calcimetry, petrographic and microfossils content. Microfossils analyses related to relatives age from the dredge samples, resulted on Pliocene and Holocene ages. Meanwhile the field samples resulted on Miocene to Holocene age. Correlations between dredge and field samples for the Jama sector were interpreted to be an intern marine shelf paleo-environment and for the Esmeraldas sector were interpreted to be marine slope. The evolution analysis of the continental margin shows that from the Pliocene, the Jama coast suffered an uplift of 50 to 100 m meanwhile the dredge area suffered subsidence. The Esmeralda’s coast suffered a major uplift of 1000 m approximately.